2013
DOI: 10.1111/tbed.12148
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection of Sheep withAnaplasma,TheileriaandBabesiaSpecies in the Kurdistan Region, Iraq

Abstract: Summary Infections of small ruminants with Anaplasma, Theileria and Babesia species are widely distributed in the old world and are of great economic impact. In Iraq, data on disease occurrence in sheep caused by above‐mentioned infectious agents are scarce. This study provides information on various haemoparasitic agents infecting sheep in the Kurdistan Region, Iraq, using molecular diagnostic tools. Altogether, 195 samples originating from three governorates in the Kurdistan Region, namely Duhok, Erbil and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 15 publications
6
30
1
Order By: Relevance
“…Despite the widespread distribution of ovine tick-borne haemoparasitic diseases in tropical and subtropical regions of the world [33] and their constraint to livestock production [1, 15, 29, 34], relatively limited information on their abundance and distribution is currently available [33]. Theileriosis and babesiosis are the two most extensively studied tick-borne haemoparasitic diseases occurring in small ruminants in Turkey; however only limited information exists on ovine anaplasmosis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the widespread distribution of ovine tick-borne haemoparasitic diseases in tropical and subtropical regions of the world [33] and their constraint to livestock production [1, 15, 29, 34], relatively limited information on their abundance and distribution is currently available [33]. Theileriosis and babesiosis are the two most extensively studied tick-borne haemoparasitic diseases occurring in small ruminants in Turkey; however only limited information exists on ovine anaplasmosis.…”
Section: Discussionmentioning
confidence: 99%
“…These two parasites have been detected in China [3, 40] and Iraq [29] and recent evidence suggests the distribution of T. luwenshuni extends as far as the UK [41]. A study conducted in Iran revealed the presence of T. luwenshuni in sheepdog isolates [42].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations